Early Breastfeeding Initiation (IMD) and Determinant Factors: A Survey of Mothers of Posyandu Visitors in the Working Area of the Mogang Health Center, Samosir Regency, Indonesia - Rotua Basaria Sitanggang; Myrnawati Crie Handini; Sri Asnawati Munthe (Community Medicine and Education Journal, 2023)
Breast milk is the best food that can help the process of growth and development of the baby. Early breastfeeding initiation is the beginning of the success of exclusive breastfeeding. This study aimed to analyze the factors associated with early initiation of breastfeeding (IMD) in mothers who visit Posyandu in the working area of the Mogang Samosir Health Center, Indonesia. This study used a qualitative approach and was conducted in the work area of the Mogang Health Center, Samosir Regency, from November 2022-July 2023. The informants in this study were 10 informants consisting of 5 mothers who had just given birth and were breastfeeding and 5 health workers (midwives, nurses). Research instrument with interview guidelines. The results of the IMD study are the first way that is done to babies half an hour after birth by placing the baby on the mother's chest to make direct contact with the mother's skin and looking for the mother's nipple to get the first milk that comes out of the mother's nipple. The benefits of IMD are that the baby can interact directly with the mother, builds closeness between the baby and the mother, and gets the first milk from the mother, which becomes the baby's immunity. How to do IMD is a baby who has been born placed on the mother's chest and taught to look for the mother's nipple. The mother's attitude in carrying out IMD has a positive impact, and the mother is happy and happy when the baby succeeds in getting to the mother's nipple and can breastfeed directly. The response regarding IMD is an action that is useful and positively received by the mother because it has good benefits for the baby and the mother. Family support for mothers in carrying out IMD means that the family supports the mother in the success of the baby to initiate early breastfeeding and helps the mother in fulfilling the need to increase milk production.